PREPARATION OF BARIUM HEXAFERRITE BY SOL GEL SELF COMBUSTION USING POLYVINYL ALCOHOL - N. Idayanti; A. Nuruddin; Suyatman Suyatman (Jurnal Sains Materi Indonesia, 2007)
PREPARATION OF BARIUM HEXAFERRITE BY SOL GEL SELF COMBUSTION USING POLYVINYL ALCOHOL. Barium hexaferrite powders were produced by sol-gel auto-combustion. Ferric and barium nitrate in the molar ratio of 1:2, and Poly Vinyl Alcohol (PVA) are used as starting materials. After gelation with ammonium hydroxide, dehydration and subsequent mechanical milling, auto combustion and calcination at temperature from 300 oC to 1250 oC were performed to produce barium ferrite powder. XRD pattern showed barium ferrite phase started to form at temperature of 500 oC and grew to single phase at 1000 oC, with hexagonal structure. At this stage, the powder has saturation and remanence magnetization of 50.9 emu/g and 33.6 emu/g, respectively, and coercivity of 2.94 kOe.